Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/cbdv.202100244
|View full text |Cite
|
Sign up to set email alerts
|

α‐Glucosidase Inhibition Action of Major Flavonoids Identified from Hypericum Attenuatum Choisy and Their Synergistic Effects

Abstract: Hypericum attenuatum Choisy is a traditional Chinese herbal plant with multiple therapeutic effects. In this study, bioactivity‐guided fractionation of Hypericum attenuatum Choisy extracts afforded three major flavonoids (including astragalin, guaijaverin and quercetin), which possessed α‐Glucosidase inhibitory activity with IC50 values of 33.90±0.68 μM, 17.23±0.75 μM and 31.90±0.34 μM, respectively. Circular dichroism analysis revealed that all the three compounds could interact with α‐glucosidase by inducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The kinetic prediction showed that kaempferol and astragalin inhibited the activity of alpha-glucosidase enzyme in a mixed manner, while the acarbose exhibited it in competitive manner. Kaempferol has been determined as both a mixed-type inhibitor [ 13 , 14 ] and a non-competitive inhibitor [ 15 ], while astragalin has been reported as a non-competitive inhibitor [ 16 ]. It is known that the competitive manner is the inhibitor bond free enzyme (E) at the active site, the uncompetitive manner is the inhibitor bond with the enzyme-substrate (ES) complex, the non-competitive manner is the inhibitor bond with the E and ES complex, and the mixed-type manner is the inhibitor bond target enzyme at more than one site [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic prediction showed that kaempferol and astragalin inhibited the activity of alpha-glucosidase enzyme in a mixed manner, while the acarbose exhibited it in competitive manner. Kaempferol has been determined as both a mixed-type inhibitor [ 13 , 14 ] and a non-competitive inhibitor [ 15 ], while astragalin has been reported as a non-competitive inhibitor [ 16 ]. It is known that the competitive manner is the inhibitor bond free enzyme (E) at the active site, the uncompetitive manner is the inhibitor bond with the enzyme-substrate (ES) complex, the non-competitive manner is the inhibitor bond with the E and ES complex, and the mixed-type manner is the inhibitor bond target enzyme at more than one site [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, compared to the control drug in the same condition, this flavonol exhibited a weak α-amylase inhibitory effect [ 27 , 33 , 48 , 117 , 118 , 139 , 142 , 158 , 160 , 165 , 170 173 ], with the pIC 50 being 4.07 (3.26–4.83). The mechanism underlying the inhibition of both enzymes remained controversial, which was documented to be in a mixed [ 141 , 149 , 172 ], non-competitive [ 142 , 155 , 166 ], or even competitive manner [ 48 , 94 , 114 , 161 , 172 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies also revealed that compounds 111–113 were weak to moderate α-amylase inhibitors. Kaempferol-3- O -β- d -glucopyranoside, also known as astragalin (109) , potently inhibited α-glucosidase as potent as acarbose, proven by at least eight studies [ 99 , 124 , 145 , 155 , 160 , 197 , 202 , 203 ]. Two out of three studies examined the α-amylase inhibition of 109 as three times weaker than the control agent [ 160 , 206 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the combination of extracts has been shown to potentially offer synergistic effects, where the combined activity of the extracts is greater than or equal to the sum of their individual activities. Synergistic interactions can lead to enhanced bioactivity, which might result in a more potent therapeutic effect than would be expected from the individual activities of the single compounds alone [ 38 40 ]. Combining plant extracts has been shown to enhance the pharmacological activity potential due to the presence of multiple compounds, leading to synergistic or additive effects.…”
Section: Discussionmentioning
confidence: 99%